1992
DOI: 10.1073/pnas.89.3.1050
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis for the nucleic acid binding cooperativity of bacteriophage T4 gene 32 protein: the (Lys/Arg)3(Ser/Thr)2 (LAST) motif.

Abstract: To identify the functional residues of the N-terminal B region of bacteriophage T4 gene 32 protein involved in its cooperative binding to single-stranded nucleic acids, a process dependent on homotypic protein-protein interaction, we have studied the interaction of the protein with synthetic peptides containing different portions of this domain. Gel-permeation chromatography showed that a 6-acryloyl-2-dimethylaminonaphthalene (acrylodan)-labeled fluorescent peptide corresponding to the first 17 residues of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 28 publications
4
47
1
Order By: Relevance
“…The central domain of the T4 gp32 contains both a zinc-finger motif and a fairly regularly spaced series of 6 tyrosine residues, features that are believed to be important to its nucleic acid binding activity (23,24). A second LAST motif is also present here and would be able to interact with either the acidic carboxyl terminal part of the same monomer when the protein is not bound to DNA, or with the nucleic acid backbone when the protein is bound to DNA (15).…”
Section: Random Genomic Sequencing Of Rb49mentioning
confidence: 98%
See 1 more Smart Citation
“…The central domain of the T4 gp32 contains both a zinc-finger motif and a fairly regularly spaced series of 6 tyrosine residues, features that are believed to be important to its nucleic acid binding activity (23,24). A second LAST motif is also present here and would be able to interact with either the acidic carboxyl terminal part of the same monomer when the protein is not bound to DNA, or with the nucleic acid backbone when the protein is bound to DNA (15).…”
Section: Random Genomic Sequencing Of Rb49mentioning
confidence: 98%
“…The T4 protein is organized in a three-domain structure. The amino terminal domain of the protein is composed of basic residues and contains a LAST motif (Lys/Arg/Lys/Ser/Thr) (15). This element is believed to be involved in the protein's cooperative binding to DNA (25,48,69,73,79).…”
Section: Random Genomic Sequencing Of Rb49mentioning
confidence: 99%
“…It has been suggested that an acidic arm of the core domain adjacent to the C-domain (within residues 200-239) might occupy the trough between the two lobes of gp32, and would therefore have to be displaced in order for ssDNA to bind. 19,43 This trough contains a patch of cationic residues Lys-Arg-Lys-Thr-Ser (the LAST motif) 43,46,47 at positions 110-114 of the core domain that was shown to bind directly to ssDNA. 17,43,46,48 In the full-length protein, displacement would involve the adjacent acidic C-domain (residues 254-301), which might find additional basic regions of the core to associate with, and thus further slow the binding process.…”
Section: Analysis Of the Experimental Unwinding Force As A Function Omentioning
confidence: 98%
“…In the absence of binding nucleic acid, the CTD could occupy the cationic trough between the two lobes of gp32 protein, where residues 110-114, Lys-Arg-Lys-Thr-Ser, were shown to bind directly to ssDNA. 3,21,44,45 The CTD would therefore have to move away in order for the DNA to bind. This model is also supported by the results of the study of the effect of the CTD on the proteolytic accessibility of the protein in the DNA-bound and unbound forms.…”
Section: Introductionmentioning
confidence: 99%